Knapp, Ronald G., China's Traditional Rural Architecture. A Cultural Geography of the Common House, Honolulu, University of Hawaii Press, 1986, XIII + 177 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1989)
-